Electromagnetic Wave Absorber Measurement in a Large Coax - Pues, H. F. (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
A large coaxial line for low- frequency absorber reflectivity measurements has been designed and built in Westerlo. It consists of a tapered 5 m long feed section and a uniform 12 m long section in which eight standard-base-size (0.61 m x 0.61 m) absorbers that are mounted on a carriage, can be inserted. Using an automatic vector network analyser, the normal-incidence metal-backed reflectivity of the inserted absorbers can be measured accurately in the 0-140 MHz frequency range. The accurate knowledge of the reflectivity in this low frequency range is critically important for the proper design of shielded semi- anechoic and fully anechoic rooms used for radiated emission and immunity testing.